2001
DOI: 10.1074/jbc.m103426200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel IκB Protein, IκB-ζ, Induced by Proinflammatory Stimuli, Negatively Regulates Nuclear Factor-κB in the Nuclei

Abstract: The transcription factor nuclear factor-B (NF-B) plays crucial roles in a wide variety of cellular functions and its activity is strictly regulated by cytosolic inhibitors known as IBs. We here report a new member of the IB protein family, IB-, harboring six ankyrin repeats at its carboxyl terminus. IB-mRNA is strongly induced after stimulation by lipopolysaccharide. The induction of IB-is also observed by stimulation with interleukin-1␤ but not by tumor necrosis factor-␣. In contrast to cytosolic IB-␣, -␤, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
319
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(339 citation statements)
references
References 31 publications
14
319
0
Order By: Relevance
“…A previous report showed that the N-terminal of NFKBIZ was important for nuclear localization (Yamazaki et al, 2001). Our results confirmed these findings, as the N-terminally truncated mutant localized to the cytoplasm.…”
Section: Fus-ddit3 Deregulates Nf-jb Target Genessupporting
confidence: 92%
See 1 more Smart Citation
“…A previous report showed that the N-terminal of NFKBIZ was important for nuclear localization (Yamazaki et al, 2001). Our results confirmed these findings, as the N-terminally truncated mutant localized to the cytoplasm.…”
Section: Fus-ddit3 Deregulates Nf-jb Target Genessupporting
confidence: 92%
“…NFKBIZ promotes transcription (Kitamura et al, 2000;Motoyama et al, 2005) but may also act as an inhibitor of p50 containing NF-kB complexes (Yamazaki et al, 2001;Totzke et al, 2006). In this study, we report that the MMP1 and LCN2 genes encoding matrix metalloproteinase 1 and lipocalin 2 (a cofactor for MMP9), both involved in extracellular matrix remodeling, are strongly expressed in FUS-DDIT3 carrying cell lines.…”
Section: Fus-ddit3 Deregulates Nf-jb Target Genesmentioning
confidence: 67%
“…In mice, there is no expression of IkBz in the resting state and it is induced by lipopolysaccharide (LPS), interleukin-1 beta (IL-b), peptidoglycan, bacterial lipoprotein, flagellin, and C P G DNA, but not by tumor necrosis factor alpha (TNFa) (Yamazaki et al, 2001;Yamamoto et al, 2004;Motoyama et al, 2005). Conversely, human IkBz expression is strongly induced by TNFa (Totzke et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Wet lab experiments have shown that human IkBz binds to the p50/p65 heterodimer, while mouse IkBz shows a preference for p50/p50 homodimer. Because it is evident that only C-terminal ARD (452-718) is capable of binding with its partners (Yamazaki et al, 2001;Motoyama et al, 2005;Totzke et al, 2006), we have concentrated solely on the C-terminal ARD in the present study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation